1974
DOI: 10.1002/ar.1091790302
|View full text |Cite
|
Sign up to set email alerts
|

On the synaptogenic sequence in the chick retina

Abstract: Study of the developing chick retina with the electron microscope revealed that dyad ribbon synapses begin to form in the inner plexiform layer before synaptic ribbons begin to appear in photoreceptor terminals of the outer plexiform layer. This centrifugal (inner to outer) sequence of synaptogenesis in the predominantly cone retina of the chick differs from the centripetal sequence that has been reported for the predominantly rod retinas of the mouse and rat. This difference does not favor the hypothesis, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 9 publications
7
74
1
Order By: Relevance
“…Photoreceptors do not differentiate morphologically until E9.5, when the inner segments appear (Meller and Tetzlaff, 1976). The outer segments appear on E13 (Meller and Tetzlaff, 1976), and the synapses from photoreceptors to bipolar cells are evident on about E18 (Hughes and LaVelle, 1974). As discussed above, we found that RaxL is expressed in developing photoreceptors, but not in mature photoreceptors on E19, suggesting that RaxL is not required for the maintenance or survival of mature photoreceptors.…”
Section: The Expression Pattern Of Raxl Suggests a Role In Early Devesupporting
confidence: 61%
“…Photoreceptors do not differentiate morphologically until E9.5, when the inner segments appear (Meller and Tetzlaff, 1976). The outer segments appear on E13 (Meller and Tetzlaff, 1976), and the synapses from photoreceptors to bipolar cells are evident on about E18 (Hughes and LaVelle, 1974). As discussed above, we found that RaxL is expressed in developing photoreceptors, but not in mature photoreceptors on E19, suggesting that RaxL is not required for the maintenance or survival of mature photoreceptors.…”
Section: The Expression Pattern Of Raxl Suggests a Role In Early Devesupporting
confidence: 61%
“…Thus, during development, in chick retina two arginine-requiring pathways appear to exist and these seem to be involved in differentiation processes and synaptogenesis. Interestingly, in chick embryo retina synapses have not been detected prior to the 13th embryonic day [19].…”
Section: Discussionmentioning
confidence: 97%
“…As the retinal pigment epithelium (RPE) becomes tightly associated with the neural retina and hampers fluorescence observations in post-hatched chicks, we carried out our analysis at E16 and earlier, the stages during which we could still separate the RPE from the associating neural retinas. Although E16 is still an embryonic stage, synaptic ribbons and vesicles are already present in the outer plexiform layer (Hughes and LaVelle, 1974), suggesting that basic neural connecting patterns are already established.…”
Section: Embryonic Chicken Retinas Have 3 Morphologically Distinct Sumentioning
confidence: 99%